Reprograming of Glucose Metabolism by Zerumbone Suppresses Hepatocarcinogenesis - Wani, Nissar Ahmad; Zhang, Bo; Teng, Kun-Yu; Barajas, Juan M; Motiwala, Tasneem; Hu, Peng; Yu, Lianbo; Brüschweiler, Rafael; Ghoshal, Kalpana; Jacob, Samson T (Molecular cancer research, 2018)
Hepatocellular carcinoma (HCC) is the most prevalent and highly aggressive liver malignancy with limited therapeutic options. Here, the therapeutic potential of zerumbone, a sesquiterpene derived from the ginger plant , against HCC was explored. Zerumbone inhibited proliferation and clonogenic survival of HCC cells in a dose-dependent manner by arresting cells at the G -M phase and inducing apoptosis. To elucidate the underlying molecular mechanisms, a phosphokinase array was performed that showed significant inhibition of the PI3K/AKT/mTOR and STAT3 signaling pathways in zerumbone-treated HCC cells. Gene expression profiling using microarray and analysis of microarray data by Gene Set Enrichment Analysis (GSEA) and Ingenuity Pathway Analysis (IPA) revealed that zerumbone treatment resulted in significant deregulation of genes regulating apoptosis, cell cycle, and metabolism. Indeed, tracing glucose metabolic pathways by growing HCC cells with C -glucose and measuring extracellular and intracellular metabolites by 2D nuclear magnetic resonance (NMR) spectroscopy showed a reduction in glucose consumption and reduced lactate production, suggesting glycolytic inhibition. In addition, zerumbone impeded shunting of glucose-6-phosphate through the pentose phosphate pathway, thereby forcing tumor cells to undergo cell-cycle arrest and apoptosis. Importantly, zerumbone treatment suppressed subcutaneous and orthotopic growth and lung metastasis of HCC xenografts in immunocompromised mice. In conclusion, these findings reveal a novel and potentially effective therapeutic strategy for HCC using a natural product that targets cancer cell metabolism. Dietary compounds, like zerumbone, that impact cell cycle, apoptosis, and metabolic processes may have therapeutic benefits for HCC patients. .